Processes controlling the seasonal cycle of wave-dominated inlets - Bertin,Xavier (2015)
This paper reviews the physical processes controlling wave-dominated inlets, based on several studies conducted at two inlets located on the West Coast of Portugal. Once the observed hydrodynamics and morphological changes are reasonably simulated, numerical experiments are performed to explain the development of the inlet during fair weather conditions and its shoaling and closure during winter storms. The former behaviour is explained by a tidal distortion that promotes ebb-dominance while the latter is explained by the combination of several wave-related processes: (1) the bulldozer effect due to the shore-normal component of wave forces; (2) the presence of lateral barotropic pressure gradients, accelerating longshore flows towards the inlet; (3) wave blocking during the ebb and (4) a rise in mean sea level, peaking in late autumn. Recent results also suggest that infragravity waves may play a major role.